GENERATIVE ARTIFICIAL INTELLIGENCE AS A STRATEGIC TOOL FOR SALES AND MARKETING IN THE MODERN WORKPLACE: A SYSTEMATIC LITERATURE REVIEW - Kumar, Pritam; Mastana, Amarjeet Singh; Satanasavapak, Punnaluck; Khanijou, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Artificial intelligence in sales and marketing is rapidly developing, allowing companies to improve personalization and responsiveness in their digital channels. GenAI has become a strategic tool in the modern workplace. Through the research presented in this paper, 38 articles on the topic of GenAI in the modern workplace were analyzed on Google Scholar, ScienceDirect, SpringerLink, and Scopus to determine how GenAI is transforming sales and marketing. Using the PRISMA model, three main research questions were answered to determine the role of GenAI in modern sales and marketing: how GenAI is transforming sales and marketing procedures, the most common applications of GenAI in sales and marketing, and how the use of GenAI impacts sales and marketing performance. The results of this literature review show that GenAI is transforming sales and marketing through the use of large language models, conversational AI, predictive analytics, and image and video generation. The most common applications of GenAI within sales and marketing include personalized content creation, campaign optimization, dynamic pricing, and sales and marketing automation. Finally, the use of GenAI in sales and marketing allows sales and marketing departments to improve their effectiveness, increase conversions, and reduce the amount of effort required to complete sales and marketing tasks. Based on these findings, a framework is proposed that models the various capabilities of GenAI, its common applications in sales and marketing, and the impact of its implementation on sales and marketing performance. Overall, this literature review helps to demonstrate GenAI’s growing strategic importance within sales and marketing departments and justifies the need for a balance between the implementation of these technologies and the oversight of those departments. Though uneven in their geographical and methodological representations of the impact of GenAI on sales and marketing departments, these findings indicate that GenAI is developing into a significant mechanism of transformation in the sales and marketing industry worldwide.